PENINGKATAN KEAMANAN JARINGAN TERHADAP SERANGAN MALWARE MENGGUNAKAN TEKNIK HONEYPOT DIONAEA - Agus Hariyanto; Surateno Surateno (Jurnal Teknologi Informasi dan Terapan, 2019)
Handling for network security issues require a defense system that uses a firewall, antivirus and intrusion detection systems in the network (network intrusion detection system / NIDS). Securi tyrelated attacks through the network with malware could use the honeypot Dionaea. In this research honeypot implementation Dionaea as a shadow server as a diversion attack, while the model of the attack through the network first scan and attack by malwar e. It is expected that the system is implemented capable of handling network security attacks. Scenario testing in this study were carried out attacks on the system via the internal network and external networks / public use nmap and metasploit. Besides te sting in realtime against attack from outside. This model of data retrieval is done for 3 days in a span of 7:00 to 3:00 p.m. On testing over a local network, the public and the public in realtime obtained the system has detected attacks. In the public backlash in realtime leads on port 1433 for MSSQL service, so it requires more handling for systems that use the service.